Synergistic Effect of Implant Surface Physicochemical Modifications and Macrogeometry on the Early Stages of Osseointegration: An In Vivo Preclinical Study - Benalcázar-Jalkh, Ernesto B.; Nayak, Vasudev Vivekanand; Slavin, Blaire V.; Balderrama, Isis Fatima [UNESP]; Bonfante, Estevam A.; Coelho, Paulo G.; Witek, Lukasz (Wiley, 2025)
This preclinical, in vivo study aimed to histologically and histomorphometrically evaluate the effect of implant design features on bone healing during the early stages of osseointegration. Three different implant macrogeometries and surface treatments were evaluated: (1) trapezoidal threads with decompressing vertical chambers and blasted acid-etched surface (Maestro/Blasted+AE); (2) large thread pitch implant with deep and wide threads, with TiUnite surface (RS/TiUnite); and (3) progressive buttress threads with SLActive surface (BL/SLActive). Implant surfaces were characterized by scanning electron microscopy, profilometry, and energy-dispersive X-ray spectroscopy. Implants were placed in the iliac bone of 12 female sheep (~65 kg and 2 years old). Following healing times of 3- and 6- weeks, samples were harvested and subjected to qualitative and quantitative histological/histomorphometric evaluations. Percentages of bone-to-implant contact (%BIC) along the implant's perimeter and bone area fraction occupancy (%BAFO) within implant threads were measured, and results were analyzed using a linear mixed model analysis. All implants, irrespective of differences in macrogeometry and surface treatment, at both healing times demonstrated successful osseointegration. Evaluations of %BIC yielded no statistically significant differences among groups at 3 and 6 weeks (p > 0.052). While no significant differences were detected among groups for %BAFO at 3 weeks (p > 0.249), Maestro/Blasted+AE yielded significantly higher degrees of bone formation within implant threads relative to RS/TiUnite (p = 0.043) and BL/SLActive group (p = 0.032) at the 6-week time point. Qualitative histological analyses depicted different osseointegration features for the different implants. While Maestro/Blasted+AE portrayed evidence of an intramembranous-like osseointegration pathway in the healing chambers and interfacial remodeling at thread tips, BL/SLActive and RS/TiUnite groups predominantly presented an interfacial bone remodeling healing pathway. Implant design features influenced the osseointegration pathway, where implants with decompressing vertical chambers enhanced bone formation between implant threads.
Keywords: dental implants; design; osseointegration; surface treatment